Em busca do tempo partido: a consciência histórica e o MST - Mara, Eduardo (2009)
The work that follows is dedicated to the study of the historic time experience by the political militancy from our time. The political militant from the left-wing is the one that denies the state of current things, recovering a historic experience located far before its time and projecting a future beyond the incessant reproduction of the present relations. We chosen the Landless Workers Movement, not as study object, but as specific place where this consciousness is made and can be comprehended. The historic consciousness study of the landless militancy is, for us, the best starting point to understand the magnification of the historical time operated on the change of social relations lived inside an organization. The time division between before and after, as well as the history being understood as a progress isn t a natural given data, but a construction that obeys the contradictions of the present. It, therefore, must understand how the present lived by the militancy operates changes on the consciousness of time. From documents, reference books, formation notebooks and several materials produced by MST, we try to understand the way that the movement tells his history and lists with this wider experience of the struggle for the change of the current social order. Similarly, when we hear reports of history of several militants, we try to comprehend how this wider narrative re-orients the sight over history himself, over the experience of contradictions on before and after making the landless militant